2022
DOI: 10.1038/s41598-022-21936-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of days alive and out of hospital as a new patient-centered outcome to quantify life impact after heart transplantation

Abstract: The number of patients waiting for heart transplantation (HTX) is increasing. Thus, identification of outcome-relevant factors is crucial. This study aimed to identify perioperative factors associated with days alive and out of hospital (DAOH)—a patient-centered outcome to quantify life impact—after HTX. This retrospective cohort study screened 187 patients who underwent HTX at university hospital Duesseldorf, Germany from September 2010 to December 2020. The primary endpoint was DAOH at 1 year. Risk factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…By excluding patients who did not survive their index hospitalisation, we were able to identify factors that affect longterm days alive and out of hospital. 26 This identified that gestational age and presence of non-cardiac anatomic defects were associated with increased rehospitalization and thus fewer days alive and out of hospital, while hybrid Norwood and right ventricular dominance no longer impacted days alive and out of hospital if a patient survived index hospitalisation. This change in variable significance of non-cardiac anatomic abnormalities in adjusted analyses has also been demonstrated in a study by Alsoufi et al 27 It is possible that children with extra-cardiac defects, after surviving their index hospitalisation, require a higher level of general care that contributes to more frequent hospitalisations in this population.…”
Section: Discussionmentioning
confidence: 96%
“…By excluding patients who did not survive their index hospitalisation, we were able to identify factors that affect longterm days alive and out of hospital. 26 This identified that gestational age and presence of non-cardiac anatomic defects were associated with increased rehospitalization and thus fewer days alive and out of hospital, while hybrid Norwood and right ventricular dominance no longer impacted days alive and out of hospital if a patient survived index hospitalisation. This change in variable significance of non-cardiac anatomic abnormalities in adjusted analyses has also been demonstrated in a study by Alsoufi et al 27 It is possible that children with extra-cardiac defects, after surviving their index hospitalisation, require a higher level of general care that contributes to more frequent hospitalisations in this population.…”
Section: Discussionmentioning
confidence: 96%
“…DAOH were calculated by subtraction of all days spent in the hospital from 365 days. In case of death, the days the patient did not survive were added to the time spent in the hospital which was then subtracted from 365 days [ 13 , 14 ]. DAOH is a more patient-centred outcome as it includes mortality, length of hospital stay and hospital readmissions and is known for its correlation with measures of quality of life [ 11 ].…”
Section: Methodsmentioning
confidence: 99%